Photoluminescence and Stability of 2D Ruddlesden–Popper Halide Perovskites - Zhilin Ren; Zhengtian Yuan; Aleksandr A. Sergeev; Ivor Lončarić; Muhammad Umair Ali; Atta Ur Rehman; Kam Sing Wong; Yanling He; Juraj Ovčar; Jasminka Popović; Aleksandra B. Djurišić (Molecules)
Two-dimensional lead halide perovskites are of significant interest for a variety of practical applications. However, the relationships between their composition and properties are not fully clear. Here we investigated photoluminescence from 2D Ruddlesden–Popper perovskites with different bulky spacer cations. Significant differences in their optical properties and stability are observed, and perovskites with benzylammonium (BZA) and phenethylammonium (PEA) were selected for more detailed investigation of the observed stability differences due to their similar structure. We find that PEA2PbI4 exhibits more narrow emission and increased stability compared to BZA2PbI4. In addition, PEA2PbI4 exhibits self-healing of defects evident from PL enhancement, which is absent for BZA2PbI4. The observed differences between perovskites with BZA and PEA spacer cations can be attributed to differences in the formation of spacer cation vacancies.